IMPLEMENTING CHARACTER EDUCATION STRATEGIES IN MAJOR ISLAMIC EDUCATIONAL INSTITUTIONS IN BANTEN PROVINCE - Ridwan, Iwan; Sirojudin, Rumbang; Wasehudin, Wasehudin (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Purpose: This study examines strategies for implementing character education in Islamic educational institutions under major Islamic organizations in Banten Province. Method: Using a qualitative case study approach, data were collected through observations, interviews, and document analysis in schools affiliated with Muhammadiyah, Nahdlatul Ulama, Mathla'ul Anwar, and Al-Khairiyah. Result: The findings indicate that character education is implemented through the integration of Islamic values into the curriculum, exemplary conduct of educators, habituation via religious and extracurricular activities, and the strengthening of school culture. Key success factors include strong institutional leadership, educator competence, supportive organizational culture, and community involvement, while the main challenges are educator inconsistency, limited parental participation, and the influence of digital media on students’ character development. Conclusion: This study contributes a contextual character education model based on Islamic values that can be adapted by Islamic educational institutions in other regions with similar socio-religious contexts